1996
DOI: 10.1073/pnas.93.19.10366
|View full text |Cite
|
Sign up to set email alerts
|

Limited up-regulation of DNA methyltransferase in human colon cancer reflecting increased cell proliferation.

Abstract: Epigenetic alterations in the genome of tumor cells have attracted considerable attention since the discovery of widespread alterations in DNA methylation of colorectal cancers over 10 years ago. However, the mechanism of these changes has remained obscure. el-Deiry and coworkers [el-Deiry, W. S., Nelkin, B. D., Celano, P., Yen, R. C., Falco, J. P., Hamilton, S. R. & Baylin, S. B. (1991) Proc. Nati. Acad. Sci. USA 88, 3470-3474], using a quantitative reverse transcription-PCR assay, reported 15-fold increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
81
0

Year Published

1998
1998
2001
2001

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(87 citation statements)
references
References 23 publications
6
81
0
Order By: Relevance
“…21 Our results of elevated DNA methyltransferase levels in leukaemia are similar to studies in colon cancer that have used quantitative RT-PCR assays, where an average of 3.7-fold 23 and 2.6-fold 24 increases in DNA MTase transcripts were reported when normalised with GAPDH. Lee et al 24 also found that the level of DNA MTase expression in colon cancer was 1.8-fold higher when normalised to actin, however, no significant elevation was detected when normalised to histone H4. Therefore these authors argue that the observed increased in DNA MTase expression was simply a reflection of the increase in cell proliferation in colon tumour cells.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…21 Our results of elevated DNA methyltransferase levels in leukaemia are similar to studies in colon cancer that have used quantitative RT-PCR assays, where an average of 3.7-fold 23 and 2.6-fold 24 increases in DNA MTase transcripts were reported when normalised with GAPDH. Lee et al 24 also found that the level of DNA MTase expression in colon cancer was 1.8-fold higher when normalised to actin, however, no significant elevation was detected when normalised to histone H4. Therefore these authors argue that the observed increased in DNA MTase expression was simply a reflection of the increase in cell proliferation in colon tumour cells.…”
Section: Discussionmentioning
confidence: 93%
“…DNA MTase expression has been assayed previously in lung, liver and colon tumour samples using a wide range of methods, including protein-based assays 21,22 and RNA-based assays 20,[22][23][24]37 and the results obtained have been variable. However, in this study we developed a standardised competitive RT-PCR assay which enabled accurate measurement of DNA MTase mRNA expression within and between samples.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a recent study of colon tumors and matched normal colonic mucosa indicated that DMT expression in tumors is only modestly increased above that seen in normal colon tissue, and the increase in DMT expression was correlated with increased histone H4 expression, a measure of S phase-speciÂźc gene expression (Lee et al, 1996). Those results were perhaps not surprising in light of the fact that DMT expression and activity are known to vary with the cell cycle (Szyf et al, 1985(Szyf et al, , 1991.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence is accumulating that a loss of normal regulation of DNA methylation (both de novo and maintenance activities) is common in cancer Baylin et al, 1998). Gross changes include extensive changes in regional levels of methylation (both increased and decreased) (Laird and Jaenisch, 1994) as well as elevated levels of DNA methyltransferase (Melki et al, 1998;Lee et al, 1996). It has also recently been reported that colon cancer cell lines can be grouped into two classes which di er in their capacity to methylate introduced retroviral genomes (Lengauer et al, 1997) this has been interpreted to indicate that while defects in mismatch repair systems are critical early events leading to cancer development, alterations to the regulation of DNA methylation may provide an alternate route.…”
Section: Discussionmentioning
confidence: 99%